Smart product-service systems - Zheng, Pai; Chen, Chun-Hsien; Wang, Zuoxu (Elsevier, 2021)
Smart Product-Service Systems draws on innovative practice and academic research to demonstrate the unique benefits of Smart PSS and help facilitate its effective implementation. This comprehensive guide explains how Smart PSS reshapes product-service design in several unique aspects, including a closed-loop product design and redesign manner, value co-creation with integrated human-machine intelligence, and solution design context-awareness. Readers in industry as well as academia will find this to be an invaluable guide to the current body of technical knowledge on Smart Product-Service Systems (Smart PSS), future research trajectories, and experiences of implementation. Rapid development of information and communication technologies, artificial intelligence, and digital technologies have driven today's industries towards the so-called digital servitization era. As a result, a promising IT-driven business paradigm, known as Smart Product-Service Systems (Smart PSS) has emerged, where a large amount of low cost, high performance smart, connected products are leveraged, together with their generated on-demand services, as a single solution bundle to meet individual customer needs. Explains what factors a company needs to consider in their transition towards digital servitization and its advantages Describes how this field relates to the sustainability movement, and how Smart PSS can be implemented in a sustainable wayIncludes detailed case studies from different industries, including DELTA Electronics Inc. Singapore (smart commercialization), COMAC aviation industry (smart manufacturing servitization), and Van High Tech (smart building services)